PENERAPAN STUDENT TEAMS ACHIEVEMENT DIVISION DISERTAI MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR SISWA PEMASARAN - -, Husna Nurdina -; -, Soetarno Joyoatmojo -; -, Sri Wahyuni - (Pendidikan Ekonomi Bidang Keahlian Khusus Tata Niaga FKIP Universitas Sebelas Maret, 2016)
This research is aimed to improve students? learning outcomes in Introduction to Business Economy in class X Marketing 1 in SMK Negeri 1 Karanganyar through the implementation of cooperative learning model Student Teams Achievement Division (STAD) with picture media. This research is a Classroom Action Research (CAR). The study was conducted in two cycles, with each cycle consisting of planning, action, observation and reflection. The subjects were 37 students of class X Marketing 1 SMK Negeri 1 Karanganyar. The source of data derived from students, teachers, and documents. The data collection techniques are observation, testing, documentation and interviews. The techniques for the validity of the data used triangulation of data sources. The data analysis used descriptive analysis technique, the technique of qualitative analysis and comparative description.The results showed that through the implementation of cooperative learning model Student Teams Achievement Division (STAD) with picture media can improve learning outcomes in Introduction to Business Economics (PEB) in class X Marketing 1 SMK Negeri 1 Karanganyar in the Academic Year 2015/2016. It was proved by an increasing in the first cycle and the second cycle. Before applied cooperative learning model Student Teams Achievement Division (STAD) with picture media of the class average value was 73.27 with a percentage of 37.84% completeness. In the first cycle class average value increased to 80.97 with the percentage of 81.08% completeness and the second cycle class average value increased to 97.35 with the percentage of completeness 100%. The conclusions of this research is the application of cooperative learning model Student Teams Achievement Division (STAD) with picture media can improve learning outcomes in Introduction to Business Economics (PEB) in class X Marketing 1 SMK Negeri 1 Karanganyar in the year of 2015/2016.ABSTRAK Tujuan Penelitian ini adalah untuk meningkatkan hasil belajar Pengantar Ekonomi Bisnis (PEB) pada siswa kelas X Pemasaran 1 di SMK Negeri 1 Karanganyar melalui penerapan model pembelajaran kooperatif tipe Student Teams Achievement Division (STAD) disertai media gambar. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK). Penelitian dilakukan dalam dua siklus, dengan tiap siklus terdiri atas perencanaan, pelaksanaan tindakan, observasi dan refleksi. Subjek penelitian adalah siswa kelas X Pemasaran 1 SMK Negeri 1 Karanganyar yang berjumlah 37 siswa. Sumber data berasal dari siswa, guru, dan dokumen. Teknik pengumpulan data adalah dengan observasi, tes, dokumentasi dan wawancara. Teknik untuk keabsahan data digunakan triangulasi sumber data. Analisis data digunakan teknik analisis deskriptif, teknik analisis secara kualitatif dan deskripsi komparatif.Melalui penerapan model pembelajaran kooperatif tipe Student Teams Achievement Division (STAD) disertai media gambar terbukti dapat meningkatkan hasil belajar Pengantar Ekonomi Bisnis (PEB) pada siswa kelas X Pemasaran 1 SMK Negeri 1 Karanganyar Tahun Ajaran 2015/2016. Hal ini terbukti ada peningkatan pada siklus I dan Siklus II. Sebelum diterapkan model pembelajaran kooperatif tipe Student Teams Achievement Division (STAD) disertai media gambar nilai rata-rata kelas adalah 73,27 dengan presentase ketuntasan 37,84%. Pada siklus I nilai rata-rata kelas meningkat menjadi 80,97 dengan presentase ketuntasan 81,08% dan pada siklus II nilai rata-rata kelas meningkat menjadi 97,35 dengan presentase ketuntasan 100%. Simpulan penelitian ini adalah penerapan model pembelajaran kooperatif tipe Student Teams Achievement Division (STAD) disertai media gambar dapat meningkatkan hasil belajar Pengantar Ekonomi Bisnis (PEB) pada siswa kelas X Pemasaran 1 SMK Negeri 1 Karanganyar tahun ajaran 2015/2016.